Integrated Attitude and Character Education Approach Based on National Primary School Curriculum - Badeni Badeni; Sri Saparahayuningsih (New Horizons in Education and Social Studies Vol. 9, 2021)
The purpose of this research is to analyze the weaknesses of the character instructional/education approach in the National primary school curriculum and to develop a conceptual approach of character instructional/education being able to instill the characters contained in the content of social studies subject of primary schools in the Indonesian National curriculum. A descriptive study was used in this research. The results of this study showed that (1) the scientific learning approach was only able to develop scientific attitudes of students and character, while sorts of other attitudes and character were very less implanted into the students self, and (2) the application of the integrated scientific instructional/education approach was able to instill the values of attitudes and characters contained in the content of social studies to the students. Information perceive that is felt positive or negative by the student will shape attitudes, attitudes will form habits, and habits will shape character.